The "is" and the "ought": How perceived social norms influence safety behaviors at work? - Fugas, C.S.; Melia, J.L.; Silva, S.A. (Journal of Occupational Health Psychology, 2011)
Despite a widespread view that social norms have an important contextual influence on health attitudes and behaviors, the impact of normative influences on safety behaviors has received very little attention. The current study proposes that supervisors' and coworkers' descriptive and injunctive safety norms influence proactive and compliance safety behaviors. Longitudinal results from 132 workers in a passenger transportation company support the link between coworkers' descriptive safety norms (at Time 1) and proactive safety practices (at Time 2). Crystallization of supervisor' injunctive safety norms (at Time 2) moderated the effect of coworkers' descriptive safety norms (at Time 1) on self-reported proactive safety behavior (at Time 2). These findings emphasize the differences between supervisors' and coworkers' descriptive and injunctive norms as sources of social influence on compliance and proactive safety behavior.